Learning SQL on SQL Server 2005 - Bagui, Sikha, 1964- (O'Reilly, 2006)
Anyone who interacts with today's modern databases needs to know SQL (Structured Query Language), the standard language for generating, manipulating, and retrieving database information. In recent years, the dramatic rise in the popularity of relational databases and multi-user databases has fueled a healthy demand for application developers and others who can write SQL code efficiently and correctly. If you're new to databases, or need a SQL refresher, Learning SQL on SQL Server 2005 is an ideal step-by-step introduction to this database query tool, with everything you need for programming SQL using Microsoft's SQL Server 2005-one of the most powerful and popular database engines used today. Plenty of books explain database theory. This guide lets you apply the theory as you learn SQL. You don't need prior database knowledge, or even prior computer knowledge. Based on a popular university-level course designed by authors Sikha Saha Bagui and Richard Walsh Earp, Learning SQL on SQL Server 2005 starts with very simple SQL concepts, and slowly builds into more complex query development. Every topic, concept, and idea comes with examples of code and output, along with exercises to help you gain proficiency in SQL and SQL Server 2005. With this book, you'll learn: Beginning SQL commands, such as how and where to type an SQL query, and how to create, populate, alter and delete tables How to customize SQL Server 2005's settings and about SQL Server 2005's functions About joins, a common database mechanism for combining tables Query development, the use of views and other derived structures, and simple set operations Subqueries, aggregate functions and correlated subqueries, as well as indexes and constraints that can be added to tables in SQL Server 2005 Whether you're an undergraduate computer science or MIS student, a self-learner who has access to the new Microsoft database, or work for your company's IT department, Learning SQL on SQL Server 2005 will get you up to speed on SQL in no time.